Removal of free fatty acid (FFA) in crude palm oil (CPO) using potassium oxide/dolomite as an adsorbent: optimization by Taguchi method - Nor Shafizah, I.; Irmawati, R.; Omar, Hishamuddin; Yahaya, M.; Alia Aina, A. (Elsevier, 2022)
In this study, potassium oxide supported on dolomite adsorbent was used as an adsorbent for free fatty acids (FFAs) treatment in crude palm oil (CPO). The characteristics of the adsorbent were determined by TGA, XRD, SEM, BET and TPD-CO2. Taguchi method was utilized for experimental design and optimum condition determination. There were four parameters and three levels involved in this study: time (30, 60, 90 min), stirring rate (300, 500, 700 rpm), adsorbent dosage (1, 3, 5 wt%) and K2O concentration (5, 10, 15 wt%). The adsorbent had a larger pore size, higher basic strength, and more basic sites in greater efficiency (63%) in FFAs removal from CPO. The optimum conditions were at 30 min time, 700 rpm stirring rate, 5 wt% adsorbent dosage and 15 wt% K2O concentration. Taguchi method simplified determination of experimental parameters and minimized the operating costs.